Inovasi Kurikulum Pendidikan Agama Islam - Wini Dirgahayu; Budiman Budiman (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This study examines the urgency and implementation of innovation in Islamic religious education curriculum in responding to the challenges of the modern era. Islamic religious education not only functions as a medium for transferring religious knowledge, but also as a means of character formation and mastery of life skills amidst the development of science and technology. Using a qualitative-descriptive research method through a literature study approach, this study analyzes the historical journey of the curriculum from pre-independence to reform, as well as the challenges and opportunities faced in innovation in Islamic higher education. The results of the study indicate that innovation in Islamic religious education curriculum is very important to improve the quality of education, integrate Islamic values ​​with technological advances, and form competent individuals in the era of globalization. However, challenges such as resistance to change, gaps in technology adoption, and the need to maintain the authenticity of religious teachings require a strategic approach. This study recommends the development of an adaptive curriculum that remains based on Islamic values ​​to realize a relevant, inclusive, and transformative Islamic religious education system for modern society.